Interactive learning in a higher education Level 1 mechanics module - Booth, Kathryn; James, Brain W (International journal of science education, 2001)
Concern has been expressed that traditional higher education programmes are producing students with a surface approach to learning, rather than the desired deep approach. The aim of this study was to encourage Level 1 students (those taking the subject for the first time at higher education level) to develop such a deeper learning approach. Changes were made to both the teaching method and the form of examination paper for a Mechanics module taken by a cohort of 52 physics students. The cooperative learning approach was used to pose conceptual questions for interactive discussion. Preand post-module the students' conceptual understanding of mechanics was tested using the Force Concept Inventory (FCI) and they also completed a Contrasted Groups Learning Styles questionnaire so that we could assign a 'deep learning index'. Additionally the students completed the Learning Styles Inventory to gain a picture of the distribution of learning styles in the class. Qualitative information concerning the reaction of both the lecturer and students to the changes was also collected using a focus group enquiry, module evaluative questionnaires and reflective comments from the lecturer. Analysis of the quantitative data showed that there was no discernible overall change in either the deep learning index or the FCI score of the students. Analysis of the qualitative data, however, showed that experience of the module by both students and lecturer had been greatly improved by the changes.